IMPROVING STUDENTS’ INTEREST IN LEARNING ENGLISH BY USING CREATIVE NARRATIVE FLASH CARD - Ranta Butarbutar; Marni Bawawa (Musamus Journal of Language and Literature, 2020)
Interesting is an essential thing needs for optimal achievement in learning English. Good interesting surely creates motivation well. As an English creative teacher is being expected familiar to using media for stimulate pupils’ Interesting, to enumerate, flash card. This paper addresses the issue of experience in using narrative flash card can be used as a media to work-up learners’ interested into learn English language. Henceforth, descriptive qualitative is a design to analysis data, whereas getting data, it used observation, interview for students and teacher. And, the results showed (1) the using of narrative flash card absolutely increasing students’ interesting to learn English significantly, (2) balancing cognitive development (3) stolen-technique to motivate learners, (4) welcoming socioaffective, (5) narrative flash card as role-play media and the lastly, gadget acquisition vocabulary. Keywords: interesting; narrative-flash card; stolen-technique